Pengaruh Penerapan Metode Scramble Terhadap Hasil Belajar Siswa Kelas 5 Tema Peristiwa Dalam Kehidupan Di Sekolah Dasar - Eva Silvia; masyhud, sulthon; finali, zetti (Universitas PGRI Adi Buana Surabaya, 2020)
This research aims to find out whether or not there is an effect of the application of the scramble method to the learning outcomes of 5th-grade students on the Events in Life theme at SDN Sumberpinang 02 Jember. This type of research is a quasi-experimental study with a pretest-posttest control group design. The subjects of this study were VA and VB grade students at SDN Sumberpinang 02 Jember with a total of 40 students. Data collection methods through interviews, observations, documents, and tests. The results of the t-test showed that the value of tcount> a table was 2.856 & gt; 0.312, so that the alternative hypothesis (Ha) was accepted and the null hypothesis (H0) was rejected. The calculation of the relative effectiveness test (ER) to determine the effectiveness of the application of scramble learning methods to student cognitive learning outcomes is 46.3% with the medium category.